2005
DOI: 10.1111/j.1364-3703.2005.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere hypervariability in Magnaporthe oryzae

Abstract: SUMMARY The gray leaf spot disease of perennial ryegrass and tall fescue is caused by the fungus Magnaporthe oryzae (anamorph = Pyricularia oryzae). A collection of single-copy and repetitive DNA markers was used to investigate genetic diversity among 22 isolates of the gray leaf spot pathogen. The single-copy DNA markers revealed only three polymorphisms among 95 restriction fragments spanning approximately 0.6% of the genome. In addition, Southern hybridization analysis and mating tests revealed that all iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 37 publications
(30 reference statements)
0
30
0
1
Order By: Relevance
“…LpKY97TEL-2 is an example of a stable telomere, with the rearrangement in single spore isolate #4 ( Figure 1B) being one of only two such alterations detected in .150 single spores analyzed to date. Recalcitrance to change does not appear to persist over the long term, however, because no telomere restriction fragments appeared to be even remotely conserved among field isolates (Farman and Kim 2005). Indeed, as reported above, the LpKY97-1A and FH clones that contain this telomere (LpKY97TEL-2 and cosmid FH10L7) were polymorphic.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…LpKY97TEL-2 is an example of a stable telomere, with the rearrangement in single spore isolate #4 ( Figure 1B) being one of only two such alterations detected in .150 single spores analyzed to date. Recalcitrance to change does not appear to persist over the long term, however, because no telomere restriction fragments appeared to be even remotely conserved among field isolates (Farman and Kim 2005). Indeed, as reported above, the LpKY97-1A and FH clones that contain this telomere (LpKY97TEL-2 and cosmid FH10L7) were polymorphic.…”
Section: Discussionmentioning
confidence: 68%
“…DNA fingerprinting studies have shown that M. oryzae isolates from prg exhibit extreme variation in their telomere profiles, even when there is little or no polymorphism at internal DNA loci (Farman and Kim 2005). In contrast, rice-infecting isolates that have similar "internal DNA" profiles to one another tend also to have highly similar telomere banding patterns (Farman 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Telomeric regions of the genome exhibit the most variation, and variation accumulates rapidly in these regions (7,9,12). For example, in Saccharomyces cerevisiae the SUC, MAL, and MEL families have expanded to different extents in strains bred to ferment different carbon sources (sucrose, maltose, and melibiose, respectively) (3,7,10,43); the subtelomeric family of FLO genes, which encode the ability to adhere to different cellular and abiotic surfaces, have expanded in some fermentation and clinical isolates (22,43,45).…”
mentioning
confidence: 99%